Biomechanics & Sports Medicine - Machulik C; Hamacher D; Lindlein K; 3; Zech A; Hollander K; 4 (Deutsche Zeitschrift für Sportmedizin, 2020)
Problem: The technology of inertial measurement units (IMU) enables the collection of running biomechanical data under in-field conditions. This paper presents a validation study of an increasingly used IMU system using a corresponding below-ground magnetic timing gate system.Methods: Thirty active healthy participants ran with an IMU located at the lumbar spine on a 60 m-section of a 400 m tartantrack. The IMUs were connected with magnetic timing gates installed below the tartan track. A photoelectric cell reference system was used for comparative analysis. Outcome measures were running speed, step length and cadence during running at slow and fast velocity. Intra-Class-Correlation (ICC), Bland-Altman analysis and regression-based Bland-Altman analysis were used to determine measurement agreement. Results: The analysis showed high measurement agreement for running speed, step length and cadence for both velocities (ICCs 0.745-0.996). Bland-Altman analysis showed high random errors and increased systematic and random errors for step length and cadence atfast running velocities. Regression-based Bland-Altman analysis indicated a systematic increase of bias (systematic error) with higher step length values.Discussion: Despite a high measurement agreement expressed by ICCs, study results also showed high error values for absolute measurements expressed by systematic and random errors for all parameters. Therefore, attention should be given to thecomparability of both measurement systems. Further research should focus on details of step length calculations as well as reliability and validity underlonger running conditions. KEY WORDS: IMU, Running, Cadence, Step Length, Biomechanics